2010
DOI: 10.3109/14767058.2010.501126
|View full text |Cite
|
Sign up to set email alerts
|

Maximum length sequence brainstem auditory evoked response in low-risk late preterm babies

Abstract: Babies born at 33-36 weeks gestation without major complications had an increased III-V interval at high-rate stimulation. This suggests that late preterm babies have a mild delay in neural conduction in the more central part of the auditory brainstem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…We further conducted a more detailed study in low-risk late preterm babies using a relatively new technique -the maximum length sequence brainstem auditory evoked response (MLS BAER). No major abnormalities were found in any MLS BAER variables, either [13]. It appears that there is no appreciable abnormality in neural maturation in late preterm babies who have no major perinatal conditions.…”
Section: Introductionmentioning
confidence: 50%
“…We further conducted a more detailed study in low-risk late preterm babies using a relatively new technique -the maximum length sequence brainstem auditory evoked response (MLS BAER). No major abnormalities were found in any MLS BAER variables, either [13]. It appears that there is no appreciable abnormality in neural maturation in late preterm babies who have no major perinatal conditions.…”
Section: Introductionmentioning
confidence: 50%
“…The amplitude in the high-risk SGA (HR-SGA) group tends to be smaller than that in the low-risk AGA (LR-AGA) group, but greater than that in the high-risk AGA (HR-AGA) group. 2012b; Li et al, 2011). No notable abnormalities were found in low-risk late preterm babies except for a marginal increase in III-V interval at high-rate stimulation.…”
Section: Impaired Brainstem Auditory Function In High-risk Sga Babiesmentioning
confidence: 67%
“…SGA birth exerts a minor additional effect on the impaired brainstem auditory function in high-risk babies born at late preterm Previous BAER and MLS BAER studies found no notable abnormalities in low-risk late preterm babies, suggesting that brainstem auditory function is basically normal in low-risk late preterm babies and that late preterm birth per se does not exert any significant effect on the immature brainstem auditory pathway (Li et al, 2011). On the other hand, there were apparent abnormalities in high-risk late preterm babies, suggesting functional impairment of the brainstem auditory pathway (Jiang et al, , 2012.…”
Section: The Impaired Brainstem Auditory Function Is Mainly Produced mentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies indicated that preterm birth adversely affects the development of the central auditory system [69]. For instance, Ribeiro et al reported that preterm neonates showed longer wave V latencies than term neonates in a tone-evoked ABR study [6].…”
Section: Introductionmentioning
confidence: 99%